Low power digital CMOS design based on adiabatic switching principles - Wang, Wen Yuan. (2009)
Adiabatic or energy recovery circuit design is a relatively new method to implement adiabatic switching concepts to achieve low power dissipation in integrated circuits. It accomplishes this goal by using an alternating voltage source to charge and discharge logic state-holding capacitances through small voltage drops. The low voltage drops in the switching devices result in minimal dissipation during transitions and the alternating voltage source allows the energy stored on the capacitors to be returned to the supply. This thesis effort encompasses the design and evaluation of the three proposed adiabatic logic families; the design of a clock supply circuit to provide the energy recovery function; the design of interface circuitry to enable the coexistence of adiabatic logic and CMOS logic on a single chip; and the application of adiabatic switching theory to the design of PLA and SRAM core circuits.